Informed Consent In Odontology Residents at The Dentistry Faculty, La Plata’s National University - Miguel, Ricardo; Zemel, Martín (Acta Bioethica, 2006)
This work is based upon the need to obtain data on the practice of informed consent carried out by dentists. Data was generated from the University Residence Program at the Dentistry Faculty, L.P.N.U., Argentina. The investigation's goal is to learn about different aspects regarding strengths and weaknesses of informed consent practice. One of the findings was that theoretical knowledge on the practice of informed consent is scarce, but the new generation of dentists is dedicating more time to it. It is imperative to include ethical and legal principles related to informed consent in all dental academic curricula.